A Telescopic, Sustainable Synthesis of the Key Starting Materials of Antipsychotic Drugs Quetiapine and Loxapine via Reductive Amidation - Hazra, Amitava; Panday, Surabhi; Gupta, Pankaj; Laha, Joydev K. (Pharmaceutical Fronts, 2025)
Quetiapine, a dibenzothiazepine derivative, is an antagonist of serotonin and dopamine. It was approved by the Food Drug and Administration for the treatment of schizophrenia in 1997 and has been used as a commonly prescribed second-generation atypical antipsychotic drug. Loxapine is a dibenzoxazepine tricyclic compound used as an antipsychotic, antagonising dopamine and serotonin receptors for the treatment of acute and chronic schizophrenia. However, the preparation of their Key Starting Materials (KSMs) in the reported synthesis routes suffers from several significant restrictions, such as multistep synthesis, harsh reaction conditions, high cost factors, and the use of reagents that are environmentally unfriendly. In this work, we aimed to explore a telescopic green process for the synthesis of dibenzo[b,f][1,4]thiazepin-11(10H)-one and 2-chlorodibenzo[b,f][1,4]oxazepin-11(10H)-one, the two KSMs required for the commercial production of quetiapine and loxapine. The process involves an intermolecular base-mediated SNAr reaction of 2-fluoro-1-nitrobenzene and methyl 2-mercaptobenzoate or methyl 2-hydroxybenzoate, followed by intramolecular reductive amidation employing sodium dithionite (Na2S2O4) as the sole reagent. The SNAr reaction was performed in the presence of K2CO3 in DMF at 90°C, followed by workup to give a crude product, which was treated with Na2S2O4 in DMSO without any prepurification to obtain the desired cyclized KSMs. Unlike the commonly used metal/acid reagent for the reduction of nitro compounds, the developed process avoids the use of any metal reagent or acidic conditions. The key features include a reduced number of steps, a telescopic process avoiding purification of the first step product, and reductive amidation of unactivated esters without any externally added activating agent.
Keywords: quetiapine; loxapine; APIs synthesis; nitro reduction; reductive amidation; sodium dithionite (Na2S2O4)